The Fourth Plan Preliminary Memorandum Government of Rajasthan - Planning Commission (Planning Commission)
The State of Rajasthan was formed as a result of the merger of number of princely States. It inherited a legacy which had hardly any parallel in the country. Very few of the covenanting States had undertaken any significant programme of development and except for the development of the Capital and some other important towns the other areas were in a sad state of neglect. The result was that when the First Five Year Plan was initiated in the year 1951 not only Were the circumstances for economic growth difficult but even the basic social services and amenities which were already available in most other parts of the country had to be provided de novo.
Government of Rajasthan Planning Department